Pengaruh Corporate Social Responsibility dan Customer Retention terhadap Business Performance Melalui Business Continuity UMKM Pertamina - Ali Fikryansyah Nuur; Donant Alananto Iskandar (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Customer Retention on Business Performance, with Business Continuity as an intervening variable, among MSMEs fostered by Pertamina in Jakarta. A quantitative approach was employed by distributing questionnaires to 160 respondents. Data were analyzed using multiple linear regression and path analysis with the help of SPSS software. The results show that CSR and Customer Retention have a positive and significant effect on Business Continuity. Both variables also have a direct impact on Business Performance. Business Continuity significantly mediates the relationship between Customer Retention and Business Performance, but does not significantly mediate the relationship between CSR and Business Performance. These findings indicate that the success of CSR programs and customer retention efforts contributes not only to short-term outcomes but also to sustaining MSME operations. This study provides practical implications for optimizing CSR strategies to enhance the competitiveness and sustainable growth of MSMEs.